The Influence Of Using Inside – Outside Circle (Ioc) Technique Toward Students’ Speaking Ability At The Second Year Of Ma Negeri 1 East Lampung - Fitrianingsih, Septi; Sholihah, Lilis (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2017)
One of the objectives in foreign language teaching in Indonesia is to improve speaking skill accurately and fluently. Speaking is one of difficult aspect for students to master. This is hardly surprising when one considers everything that is involved when speaking: ideas, what to say, language, how to use grammar and vocabulary pronunciation as well as listening to and reacting to the person you are communicating with. The purpose of this research is to know there is any positive and significant influence of using Inside Outside Circle (IOC) technique toward students’ speaking ability at the second year students of MA Negeri 1 East Lampung academic year 2016/2017. This research is quantitative research. Research design that is used in this research is quasi experimental design. Data collecting technique of this research consists of pretest, treatment and posttest. The researcher gives test to know how far the students ability in speaking. The score of the students get from pretest and posttest. Inside Outside Circle influence the students’ speaking ability. It is appropriate with the result of the students score. It was proved based on the result of ttest, where tcount was 15,89 were higher than ttable was 2.0 in significance level 5% and 2,66 in significance level 1%. It means that there is an influence of Inside Outside Circle technique toward students speaking ability in second year of MA Negeri 1 East Lampung.